2014
DOI: 10.1002/lary.24883
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of steroids for edema and ecchymosis after Rhinoplasty: A meta‐analysis

Abstract: Perioperative administration of steroid during rhinoplasty could reduce the level of edema and eyelid ecchymosis. Multiple-dose administration of steroids has more advantages in terms of the outcomes of late postoperative edema and ecchymosis compared to a single-dose regimen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 23 publications
0
41
0
1
Order By: Relevance
“…Repeated doses were found to be more effective than a single-dose steroid regimen. 8 Gun et al investigated the effects of combination of lidocaine and adrenalin injections on postoperative edema and ecchymosis. 9 They concluded that the application of a combination of lidocaine and adrenalin may reduce bleeding during rhinoplasty.…”
Section: Discussionmentioning
confidence: 99%
“…Repeated doses were found to be more effective than a single-dose steroid regimen. 8 Gun et al investigated the effects of combination of lidocaine and adrenalin injections on postoperative edema and ecchymosis. 9 They concluded that the application of a combination of lidocaine and adrenalin may reduce bleeding during rhinoplasty.…”
Section: Discussionmentioning
confidence: 99%
“…Kargı et al demonstrated that preoperative and intraoperative (as well as on postoperative days 1 and 2) intravenous administration of dexamethasone of 8 mg reduced edema and ecchymosis (2). Studies show that preoperative administration of steroids reduced edema and ecchymosis, and repeated administration of steroids was more effective than administration of a single dose (5,14). A study performed by Koşucu et al reported that keeping intraoperative mean arterial blood pressure at 50-60 mmHg reduced edema and ecchymosis (15).…”
Section: Discussionmentioning
confidence: 99%
“…Many technical measures can be instituted to decrease the incidence and severity of post-operative edema and ecchymosis; these include the use of sharp small osteotomes [12, 14], preservation of the periosteal attachment [7], cold compresses [10], and the possible use of a looped drainage tube [15]. In addition, administration of perioperative steroids [9, 16] and remifentanil with controlled hypotension may further contribute to lessen periorbital edema and ecchymosis [17]. Ineffective measures, despite being widely practiced, include infiltration with lidocaine-adrenaline combination [1, 18] and administration of arnica [11].…”
Section: Discussionmentioning
confidence: 99%